The design of a schoolchildren identification and transportation tracking system - Kalid, K.S. (IEEE Computer Society, 2017)
In Malaysia, five million children commute to school daily. There are approximately 40 percent of children use public and private vehicles to school. The busy schedule and hectic working lives of the parent are causing them not able to monitor the safety of their children in commuting to and from school. This project presents the design of a prototype, called KidBus.Tracker that tracks schoolchildren in school vehicles. The design includes the use of global positioning satellite (GPS) tracking as a way to track the school vehicle, while passive radio frequency identification (RFID) technology was used to record the children's presence in the vehicle. The data logged by the hardware would then be extracted and fed to a website in real-time. Parents would be able to monitor the school vehicle's movement while their children are on board through the KidBus.Tracker website. © 2017 IEEE.